Policy Implementation of Sending Problematic Students to Military Barracks: A Multi-Stakeholder Perspective Analysis in West Java - Nurfazriah, Aninda; Khotimah, Siti Nurul; Makarim, Mochamad Hanif; Septiany, Putri Bella; Jamiludin, Azam (Social Impact Journal, 2025)
The handling of problematic students in schools has become an important issue in the world of education, especially when the policies taken cause controversy. One policy that has attracted a lot of public attention is sending troubled students to military barracks as a form of character building and discipline. This policy has sparked debate in the community because it involves approaches, educational values, and long-term impacts on the psychological development of students. This research also aims to analyze the implementation of the policy from various perspectives, including local government, school, parents, students and psychology education experts. The method used is qualitative with a case study approach. Data were collected through documentation studies and secondary interview analysis. The results showed that the policy of sending troubled students to military barracks reaped pros and cons, although it received support from several parties because it was considered to form discipline and character, many parties considered the militaristic approach was not in accordance with the principles of humanistic education and had the potential to cause psychological impacts and violations of human rights. This research concludes that in an effort to foster troubled students, the approach should pay attention to the balance between discipline and empathy, and prioritize pedagogical principles and the protection of children's rights. Therefore, a more participatory, evidence-based policy formulation is needed and involves the active role of all parties to create a fair and effective education system in dealing with deviant behavior in the school environment. Keywords: Education policy, Problem students, Military barracks, Multi-stakeholder perspective, West Java.